2016
DOI: 10.1097/fch.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Do the Features, Amenities, and Quality of Physical Activity Resources Differ Between City and County Areas of a Large Rural Region?

Abstract: The goal of this work was to provide a community-academic partnership with actionable information for physical activity (PA) for a rural health-disparate region. Identified PA outlets were audited and combined with survey data for 813 residents in the region. Less than a third of sampled residents (28%) met PA recommendations, with low perceptions of safety for PA. PA resource outlets in rural areas had higher numbers of incivilities. On the basis of our findings, 4 actionable strategies are recommended: share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…We also examined perceptions of access to various PA domains. Our findings generally support past research that documents that supportive PA environments are less available in rural areas than in nonrural areas ( 24 , 27 , 28 ). Only the area around one’s home varied by neighborhood rurality; however, all domains varied by race and most also varied by annual household income.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also examined perceptions of access to various PA domains. Our findings generally support past research that documents that supportive PA environments are less available in rural areas than in nonrural areas ( 24 , 27 , 28 ). Only the area around one’s home varied by neighborhood rurality; however, all domains varied by race and most also varied by annual household income.…”
Section: Discussionsupporting
confidence: 91%
“…In multivariable analyses, we found that residents in these rural counties who reported a more favorable PA environment were more likely to engage in LTPA. Although most studies of the environment and PA have focused on urban and suburban environments, several studies have documented associations in rural populations, albeit with varied dimensions emerging as salient ( 12 , 13 , 22 24 ). Of the 5 PA environment domains we examined, town center connectivity was significantly associated with LTPA in multivariable models.…”
Section: Discussionmentioning
confidence: 99%
“…Preserving rural health depends, in part, on the implementation of policies that address the socioeconomic disadvantage within schools. These policies should focus on providing essential health-related initiatives for PA promotion (e.g., incorporating PA breaks and funding programs) as well as access to healthcare, and transportation, all of which are crucial for enhancing the health and well-being of children [ 15 , 16 ]. Moreover, children from lower socioeconomic households often face social stigma, feel unwelcome on school teams, lack prerequisite sports equipment/apparel, and deal with financial hardships [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children living within rural communities and from families with low-socioeconomic status (SES) often have less access and greater barriers to PA opportunities, lower health literacy, and less educational attainment, all of which are associated with lower PA participation rates and greater lifetime risk of developing CVD ( 4 , 15 , 16 ). Moreover, rural schools facing socioeconomic disadvantage are the least likely to offer policies (e.g., mandatory recess, economic development initiatives) and services (e.g., transportation, access to quality health services, and college and career readiness programs) that support PA programs ( 14 , 17 ). Further, children from lower socioeconomic backgrounds are significantly more likely to feel unwelcome on school teams and not be able to afford to participate ( 16 ).…”
Section: Introductionmentioning
confidence: 99%